Postnatal Corticosteroids Policy for Very Preterm Infants and Bronchopulmonary Dysplasia - Nuytten, A (2020)
Introduction: Postnatal corticosteroids (PNC) are effective for reducing bronchopulmonary dysplasia (BPD) in very preterm neonates but are associated with adverse effects including an increased risk of cerebral palsy. PNC use in Europe is heterogeneous across regions. This study aimed to assess whether European neonatal intensive care units (NICUs) with a low use of PNC or an explicit policy to reduce PNC use had higher risks of mortality or BPD. Methods: We included 3,126 infants in 105 NICUs born between 24 + 0 and 29 + 6 weeks’ gestational age in 19 regions in 11 countries in the EPICE cohort. First, we identified clusters of NICUs using hierarchical clustering based on PNC use and BPD prevalence and compared case mix and mortality between the clusters. Second, a multilevel analysis was performed to evaluate the association between a restrictive PNC policy and BPD occurrence. Results: There were 3 clusters of NICUs: 52 with low PNC use and a low BPD rate, 37 with low PNC use and a high BPD rate, and 16 with high PNC use and a medium BPD rate. Neonatal mortality did not differ between clusters (p = 0.88). A unit policy of restricted PNC use was not associated with a higher risk of BPD (odds ratio 0.68; 95% confidence interval: 0.45–1.03) after adjustment. Conclusion: Up to 49% of NICUs had low PNC use and low BPD rates, without a difference in mortality. Infants hospitalized in NICUs with a stated policy of low PNC use did not have an increased risk of BPD.